Investor recognition, liquidity, and post-issue performance following rights offerings: Evidence from a frontier market - Velayutham, E. (Faculty of Management Studies & Commerce, University of Jaffna, 2019)
This paper examines changes in investor recognition and liquidity around rights offerings in a frontier market, viz., Sri Lanka. We find that offer characteristics such as issue proceeds and offer price discounts improve investor recognition. We find that larger offer price discounts and offer proceeds are associated with increases in investor recognition. Further, we find that announcements of rights issues reduce information asymmetry and as a result, liquidity improves in the post rights issue announcement period. In addition, we find a strong positive association between liquidity improvements and increases in investor recognition. Finally, we find that greater investor recognition is negatively associated with contemporaneous and post- issue abnormal stock returns, whereas increases in liquidity are positively associated with post-issue abnormal returns. Overall, we show that rights issues in a frontier market affect both investor recognition and liquidity.
Keywords: Investor recognition; stock market liquidity; post-issue performance; rights offerings